Effectiveness of active learning strategies for soil science course / Salwa Adam and Nur Firdaus Abdul Rashid - Adam, Salwa; Abdul Rashid, Nur Firdaus (UiTM Press, 2020)
Common teaching methodologies which are teacher-centered learning do not enhance students' engagement and encourages passive learning which does not develop higher-order thinking. Thus, it contributed to low students' performance which caused increasing failure rate for soil science course continuously within three semesters. Active learning can foster the growth of thinking skills through participation among students and lecturer. The aim of this study to compare the effectiveness of two different type of teaching method applied for soil science course. Participants were randomly selected from Diploma Planting Industry Management (AT110) students from Faculty of Plantation and Agrotechnology. Soil science course was conducted through traditional method or teacher-centered learning in second semester of 2016. Student performances for the semester were analysed and students who were failed and have to repeat the course were identified. Those students who repeat the course was re-enrolled the course for first semester of 2017.